The eEgg: Evaluation of a New Device to Measure Pain - Böing-Meßing, Dshamilja M.; Tomschi, Fabian; Cegla, Thomas; Hilberg, Thomas (Frontiers in Physiology, 2022)
Aim: The aim of this study was to evaluate whether pain stimuli can be measured validly and reliably by the eEgg (electronic Egg), a new device to measure pain intensity, in comparison to the hand dynamometer. Methods: This study consists of screening and diagnostic tests conforming to the standard criterion of handgrip strength measurement. Fifty healthy participants (25 women, 25 men; age, 39.1 ± 13.7 years) participated in this study. The approach of intermodal comparison was used to transfer different degrees of pain sensations into measurable handgrip strength values. This included an intensity comparison of 10-100% of the subjective maximum handgrip strength and an application of thermal stimuli of 34-48°C. The eEgg was compared to the numeric rating scale (NRS) as a categorization method regarding the subjective assessment of pain. An online questionnaire was distributed to test the evaluation of the product’s features. Results: Regarding the experiment’s validity, the handgrip strength values showed significant (p<0.05) positive correlations between the eEgg and the hand dynamometer (intensities: r=0.328 to r=0.550; thermal stimuli: r=0.353 to r=0.614). The reliability results showed good to very good correlations (p<0.05) in the calculated ICC (intraclass correlation coefficient) values between the individual measurement devices: eEgg intensities: ICC=0.621 to 0.851; thermal stimuli: ICC=0.487 to 0.776 and hand dynamometer intensities: ICC= 0.789 to 0.974; thermal stimuli: ICC=0.716 to 0.910. Conclusion: The new eEgg device shows strong correlations with the hand dynamometer. The central limitation focuses on the obligatory use of an arbitrary unit (AU) for the eEgg. The results of the study indicate that this device can be used in medical and therapeutic practice in the future.